2016
DOI: 10.1371/journal.pone.0164738
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Pine Beetle Dynamics and Reproductive Success in Post-Fire Lodgepole and Ponderosa Pine Forests in Northeastern Utah

Abstract: Fire injury can increase tree susceptibility to some bark beetles (Curculionidae, Scolytinae), but whether wildfires can trigger outbreaks of species such as mountain pine beetle (Dendroctonus ponderosae Hopkins) is not well understood. We monitored 1173 lodgepole (Pinus contorta var. latifolia Doug.) and 599 ponderosa (Pinus ponderosa Doug. ex Law) pines for three years post-wildfire in the Uinta Mountains of northeastern Utah in an area with locally endemic mountain pine beetle. We examined how the degree an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Within the first group of studies focusing on impacts of fire on natural assets, ecological values and ecosystem services, a preeminent role was played by papers addressing damages and disturbances to forest ecosystem dynamics (Wu & Kim, 2013;Aleksić et al, 2009), direct changes to dominant vegetation and biodiversity (Adams, 2013) and indirect shifts caused by grass invasion (Morais et al, 2021;Kerns et al, 2020), higher impacts of pest and diseases on plant survival, variations in traits expression (Lerch et al 2016;Bélanger et al, 2013;Salazar et al, 2020), and reduction in forest resilience (Wu & Kin, 2013, Mouillot et al, 2005. Less investigated are impacts on water and soils.…”
Section: Resultsmentioning
confidence: 99%
“…Within the first group of studies focusing on impacts of fire on natural assets, ecological values and ecosystem services, a preeminent role was played by papers addressing damages and disturbances to forest ecosystem dynamics (Wu & Kim, 2013;Aleksić et al, 2009), direct changes to dominant vegetation and biodiversity (Adams, 2013) and indirect shifts caused by grass invasion (Morais et al, 2021;Kerns et al, 2020), higher impacts of pest and diseases on plant survival, variations in traits expression (Lerch et al 2016;Bélanger et al, 2013;Salazar et al, 2020), and reduction in forest resilience (Wu & Kin, 2013, Mouillot et al, 2005. Less investigated are impacts on water and soils.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, unbaited panel traps can be very useful at relatively higher D. ponderosae populations (Schmitz, ; Boone et al ., ). Likewise, in sites where tree attack rates are characteristic of the beetle's ‘incipient’ (Carroll et al ., ; Safranyik & Carroll, ) population phase, such as in our Wyoming site (Table ) and a previous study in Utah (Lerch et al ., ), unbaited panel traps generated data amenable to statistical analysis. However, in sites where tree attack rates are very low and characteristic of the beetle's endemic (Carroll et al ., ; Safranyik & Carroll, ) phase, such as our Montana site, captures in unbaited traps were too low for evaluating D. ponderosae , predator or competitor communities.…”
Section: Discussionmentioning
confidence: 99%
“…Insect sampling was performed using unbaited, flight‐intercept panel traps similar to those described previously (Schmitz, ; Tabacaru & Erbilgin, ; Lerch et al ., ). These traps were constructed from two clear Plexiglass panels (0.3 × 1 m) fitted together at a right angle.…”
Section: Methodsmentioning
confidence: 97%
“…Reciprocally, fire effects on MPB population activity are also time-dependent. Although fire-weakened trees are most susceptible to attack in the months after severe fire injury (Davis et al 2012;Lerch et al 2016;Parker et al 2006;Powell et al 2012), wildland fires can affect beetle activity indirectly over longer time periods by altering forest composition and structure (e.g., removing fire intolerant species) and providing increased water, light, and nutrients for surviving trees (i.e., growth release), thus influencing availability and vigor of suitable host trees (Fettig et al 2007;Hessburg et al 2005;Keeling and Sala 2012). In addition, occurrence of stand-replacing fires can reduce the likelihood of MPB attack until regenerating forests have attained a threshold diameter sufficient to attract beetles, especially when beetle populations are at relatively low levels (Kulakowski et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although MPB was rarely considered a major contributor to post-fire pine mortality historically (Geiszler et al 1980;McHugh and Kolb 2003;Six and Skov 2009), recent findings indicate that MPB may indeed be attracted to multiple fire-injured pine species and that the likelihood of mass attack and subsequent tree mortality was positively associated with several measures of fire injury, including crown scorch and cambial death (Davis et al 2012;Lerch et al 2016). Fires can therefore contribute to maintaining local MPB populations (Elkin and Reid 2004;Powell et al 2012), but MPB response was found to pulse and recede within two years post-burn, thereby rarely generating sustainable outbreak populations with the potential for spread to adjacent stands (Davis et al 2012;Powell et al 2012).…”
Section: Introductionmentioning
confidence: 99%